Emissions Trading with Clean-up Certificates: Deterring Mitigation or Increasing Ambition? - Kai Lessmann; Friedemann Gruner; Matthias Kalkuhl; Ottmar Edenhofer (CESifo GmbH, 2024)
We analyze how conventional emissions trading schemes (ETS) can be modified by introducing ”clean-up certificates” to allow for a phase of net-negative emissions. Clean-up certificates bundle the permission to emit CO2 with the obligation for its removal. We show that demand for such certificates is determined by cost-saving technological progress, the discount rate and the length of the compliance period. Introducing extra clean-up certificates into an existing ETS reduces near-term carbon prices and mitigation efforts. In contrast, substituting ETS allowances with clean-up certificates reduces cumulative emissions without depressing carbon prices or mitigation in the near term. We calibrate our model to the EU ETS and identify reforms where simultaneously (i) ambition levels rise, (ii) climate damages fall, (iii) revenues from carbon prices rise and (iv) carbon prices and aggregate mitigation cost fall. For reducing climate damages, roughly half of the issued clean-up certificates should replace conventional ETS allowances. In the context of the EU ETS, a European Carbon Central Bank could manage the implementation of clean-up certificates and could serve as an enforcement mechanism.
Keywords: H23; Q54; Q58; 330